First record of the sicklefin devilray Mobula tarapacana (Myliobatiformes: Mobulidae) from Australian waters - Duffy, Clinton A.j.; Vogiatzis, Anton (Zootaxa, 2016)
The sicklefin devilray Mobula tarapacana (Philippi, 1892) is one of the largest and least known mobulids (Compagno & Last 1999; Couturier et al. 2012). Collections, fisheries bycatch data and visual records suggest it is primarily oceanic, with a circumglobal tropical and warm temperate distribution (Notarbartolo-di-Sciara 1987; Compagno & Last 1999; Gadig & Sampaio 2002; White et al. 2006a, b; Weir et al. 2012; Sobral 2013; Tomita et al. 2013). In the Pacific Ocean it has been recorded from Chile, Gulf of California, Japan, Taiwan, South China Sea and Indonesia (Compagno & Last 1999; White et al. 2006b; Couturier et al. 2012; Tomita et al. 2013).